Trends in CV mortality among patients with known mental and behavioral disorders in the US between 1999 and 2020 - Ebert, Tanya; Hamuda, Nashed; City-Elifaz, Efrat; Kobo, Ofer; Roguin, Ariel (Frontiers in Psychiatry, 2023)
Introduction Patients with mental disorders are at increased risk of cardiovascular events. We aimed to assess the cardiovascular mortality trends over the last two decades among patients with mental and behavioral co-morbidities in the US. Methods We performed a retrospective, observational study using the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) Multiple Cause of Death dataset. We determined national trends in age-standardized mortality rates attributed to cardiovascular diseases in patients with and without mental and behavioral disorders, from 1999 to 2020, stratified by mental and behavioral disorders subtype [ICD10 codes F], age, gender, race, and place of residence. Results Among more than 18.7 million cardiovascular deaths in the United States (US), 13.5% [2.53 million] were patients with a concomitant mental and behavioral disorder. During the study period, among patients with mental and behavioral disorders, the age-adjusted mortality rate increased by 113.9% Vs a 44.8% decline in patients with no mental disorder (both p<0.05). In patients with mental and behavioral disorders, the age-adjusted mortality rate increased more significantly among patients whose mental and behavioral disorder was secondary to substance abuse (+532.6%, p<0.05) than among those with organic mental disorders, such as dementia or delirium (+6.2%, P− nonsignificant). Male patients (+163.6%) and residents of more rural areas (+128–162%) experienced a more prominent increase in age-adjusted cardiovascular mortality. Discussion While there was an overall reduction in cardiovascular mortality in the US in the past two decades, we demonstrated an overall increase in cardiovascular mortality among patients with mental disorders.